Current status of maintenance therapy for advanced ovarian cancer - Joanie Mayer Hope; Stephanie V Blank (Dove Medical Press, 2009)
Joanie Mayer Hope, Stephanie V BlankNew York University School of Medicine, Division of Gynecologic Oncology, New York NY, USAAbstract: Even after countered with and responding to maximal surgical and chemotherapy efforts, advanced ovarian cancer usually ultimately recurs. One strategy employed to forestall recurrence is maintenance chemotherapy, an extension of treatment following a complete response to conventional measures. Many agents have been studied and many more are currently under investigation in maintenance regimens. While phase III data suggest that taxane maintenance prolongs progression-free survival, no overall survival benefit has been established. This article reviews the current status of maintenance therapy for advanced ovarian cancer, including phase III evidence and new and upcoming trials.Keywords: maintenance therapy, consolidation therapy, advanced ovarian cancer